Opinion 2424: Columba domestica livia Gmelin, 1789 and Columba oenas domestica Linnaeus, 1758 (Aves, Columbidae): specific and subspecific names conserved for Columba livia and Columba livia domestica - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature (ICZN) has used its plenary power to conserve existing usage of the name Columba livia Gmelin, 1789 for the common domestic pigeon by granting it precedence over the senior subjective synonyms C. domestica Linnaeus, 1758, C. gutturosa Linnaeus, 1758, and C. cucullata Linnaeus, 1758. The ICZN has also used its plenary power to conserve existing usage of the trinomen Columba livia domestica Linnaeus, 1758 by setting aside Article 24.1 of the Code and granting domestica Linnaeus, 1758 precedence over gutturosa Linnaeus, 1758 and cucullata Linnaeus, 1758 whenever either of the latter two are considered a synonym of it.
Keywords: Nomenclature; taxonomy; Columba livia; Columba domestica; rock dove; feral pigeon